Machine Maintenance Scheduling Design Using Reability Centered Maintenance (RCM) method and Maintenance Value Stream Mapping (MVSM) at XYZ - Nico Pranata Mulya (PT Inovasi Pratama Internasional, 2023)
The problem in this study is the occurrence of damage to the Oven, Mixer, Bread Sicer, Proofer, Despositor, Breadline, Vacuum sealer machines. XYZ has not yet scheduled planned maintenance on production machines. The purpose of this study is to determine the reliability of the machine in operating according to the desired function for a certain period of time at XYZ and to design machine maintenance scheduling at XYZ. This research is a quantitative research with the method used is Reability Centered Maintenance (RCM) and Maintenance Value Stream Mapping (MVSM). The data used is secondary secondary data obtained from XYZ, namely data on damage to Oven, Mixer, Brread Slicer, Proofer, Despositor, Breadline, Vacuum sealer machines in 2021. The results of this study state that the reliability of the machine operates according to its function states that Ovens had an average operating time of about 584 hours between 5 failures, breadslicer machines had an average time of about 1460 between 2 failures, proofer machines had an average time of about 1460 hours between 2 failures, breadline machines had an average time of about 1460 hours between 2 failures, vacuum sealers have an average time of about 2920 hours between 1 failure, and deposit machines have an average time of 2920 hours between 1 failure. Designing proper machine maintenance scheduling for XYZ, namely Mixer maintenance or replacement every 30 days, Depositors every 60 days, ovens every 90 days, proofers every 120 days, breadline siever 60 days, bread silicer every 60 days and vacuum sealer every 30 days.